2016
DOI: 10.1002/jcad.12057
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nonsuicidal Self‐Injury and Suicidal Ideation

Abstract: This correlational study was conducted with 403 undergraduate college students from 2 universities. The authors used path analysis and bootstrap regression to analyze the relationships between variables. Locus of control and family connectedness related to current nonsuicidal self‐injury (NSSI) engagement. However, when entered into the same regression, the variables current NSSI engagement and current NSSI number of methods used mediated all other relationships with suicidal ideation. Implications to current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 55 publications
(79 reference statements)
4
33
0
1
Order By: Relevance
“…In contrast, almost 75% of those who screened positive on any measure screened positive on the DSHI, and almost 90% of those who screened positive on any measure screened positive on the ISAS. The positive screen rate of 30% on the checklist measures is similar to the 25% positive screen rate that Klonsky and Olino (2008) and Wester et al (2016) found when using checklist measures in college samples. Similarly, our positive screen rate of 13% on the simple screen is similar to the positive screen rate of 12% that Heath et al (2008) found when using a one‐item simple screen in a college student sample.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, almost 75% of those who screened positive on any measure screened positive on the DSHI, and almost 90% of those who screened positive on any measure screened positive on the ISAS. The positive screen rate of 30% on the checklist measures is similar to the 25% positive screen rate that Klonsky and Olino (2008) and Wester et al (2016) found when using checklist measures in college samples. Similarly, our positive screen rate of 13% on the simple screen is similar to the positive screen rate of 12% that Heath et al (2008) found when using a one‐item simple screen in a college student sample.…”
Section: Discussionsupporting
confidence: 82%
“…N onsuicidal self‐injury (NSSI)—that is, the deliberate harming of one's body tissue without the intention of committing suicide and not for socially sanctioned reasons (Klonsky, Muehlenkamp, Lewis, & Walsh, 2011)—has received attention among counselors working with college student populations. In a recent study of NSSI in a college sample, researchers found a prevalence rate of 25% (Wester, Ivers, Villalba, Trepal, & Henson, 2016). Other researchers have reported even higher prevalence rates, such as a 35% lifetime NSSI prevalence rate (Gratz, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Coefficient-α for the present study was .80 (95% CI [.76, .83]). This instrument was selected for inclusion as a measure of past and future suicidal ideation and behaviors, which have been empirically linked to nonsuicidal self-injury and self-harm in general (e.g., Wester, Ivers, Villalba, Trepal, & Henson, 2016). An association between scores on SBQ-R and maladaptive behavior tendency was expected based on previous research linking scores on SBQ-R with measures of self-harm (Gutierrez et al, 2001; Manca, Presaghi, & Cerutti, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to recent incidents good therapeutic relationships were reported, which were perceived to reduce negative feelings as a consequence of self-harm and/or suicidal behaviour. This is perhaps unsurprising since there is clear evidence that relationships are central to recovery and well-being (Tew et If self-harm becomes more familiar, inhibition may be reduced as non-suicidal self-injury desensitises an individual to self-harm, thereby increasing acquired capability to attempt suicide (Wester et al, 2016). A previous study of self-harm in psychiatric inpatients found it to be highly contagious, with clusters of incidents (Beasely, 1999).…”
Section: Desensitisationmentioning
confidence: 99%